Selectivity of Ni/Al LDH Material Supported by Green Tea Leaf (Camellia sinensis) Extract as an Adsorbent for Removing Cationic Dyes in Wastewater Treatment - Amri, Amri; Wibiyan, Sahrul; Fitri, Erni Salasia (Indonesian Journal of Material Research, 2025)
Water pollution due to synthetic dye waste is a serious environmental problem, so an effective method is needed to overcome it, including using adsorption. In this study, Ni/Al-Cs materials were synthesized and characterized to evaluate their selectivity towards Rhodamine B (RhB), Malachite Green (MG), and Methylene Blue (MB) dyes. Adsorption selectivity tests were conducted using UV-Vis spectroscopy to determine changes in dye concentration before and after interaction with the material. Results showed that Ni/Al-Cs had the highest adsorption capacity towards MG, followed by MB and RhB. With its selective adsorption properties, Ni/Al-Cs material has the potential to be used as an effective adsorbent in the treatment of dye effluents in aquatic environments, especially MG dye.